Quantitative and qualitative evaluation of an automated planning solution for prostate radiotherapy - Costea, Madalina\\-Liana; Ungun, Baris; Vauclin, Remi; Delasalles, Edouard; Mengin, Elie; Bus, Norbert; Gungor, Gorkem; Moll, Matthias; Cozzi, Salvatore; Gregoire, Vincent; Fenoglietto, Pascal; Paragios, Nikos (ELSEVIER IRELAND LTD, 2024)
Annual Meeting of the European-Society-for-Radiotherapy-and-Oncology (ESTRO), Glasgow, ENGLAND, MAY 03-07, 2024
Keywords: auto\\-planning; prostate cancer; blinded study